PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) DALAM SETTING PEMBELAJARAN KOOPERATIF TIPE TGT DAN GI TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR KIMIA PESERTA DIDIK SMAN 1 AIKMEL - Baiq Ismayawati; Agus Abhi Purwoko; Muntari - (Jurnal Penelitian Pendidikan IPA, 2016)
This study aims to describe the differences in critical thinking skills and chemistry learning achievement between learners who follow the model of problem-based learning (PBL) in cooperative learning settings TGT and GI at the rate of material reaction. The research is a quasi-experimental research design with pretest-posttest non equivalent control group designe with sample XI IPA 1 and XI IPA 2 are determined by random selection technique based on similarity mean value of daily tests I. Experiential learning and learner response is estimated to affect more significant learning achievement in the classroom PBM setting GI as evidenced by the average N-Gain learning outcomes in the classroom PBM setting GI of 0.43 and the average N-Gain learning achievement in the classroom PBM setting TGT of 0.32. The differences are also evidenced by the results of the hypothesis test showed a significance value of 0.002 (p <0.05). While based on the calculation of the average critical thinking skills in mind that PBM setting TGT has a more significant effect than the PBM GI settings as evidenced by the difference in the value of critical thinking skills after learning process (posttest) and prior to the learning process (pretest) on PBM classroom setting TGT and PBM GI settings are respectively 19.93 and 14.42. While the test is based on differences in critical thinking skills, it is known that there are differences between classes of critical thinking skills PBM settings TGT and PBM settings GI as evidenced by the significant value of 0.018 (p <0.05).Keywords: PBM setting TGT, PBM setting GI, critical thinking skills, learning achievement of chemistry.